The Dala law
1 online resource (xii, 86 pages)
Keywords: "The Dala Law is known through only one remaining medieval manuscript, written c.1335 - 1353, and shows strong influence from older Swedish provincial law. It is one of the oldest known texts revealing details of life and conditions in Dalar during the thirteenth and early fourteenth centuries. With an Introduction that places Dalar in its geographical, judicial, and ecclesiastical contexts, The Dala Law is an essential resource for all students and scholars interested in medieval Swedish history"--